2009
DOI: 10.1128/cvi.00336-08
|View full text |Cite
|
Sign up to set email alerts
|

Foal Monocyte-Derived Dendritic Cells Become Activated uponRhodococcus equiInfection

Abstract: Susceptibility of foals to Rhodococcus equi pneumonia is exclusive to the first few months of life. The objective of this study was to investigate the immediate immunologic response of foal and adult horse antigen-presenting cells (APCs) upon infection with R. equi. We measured the activation of the antigen-presenting major histocompatibility complex (MHC) class II molecule, costimulatory molecules CD40 and CD86, the cytokine interleukin-12 (IL-12), and the transcriptional factor interferon regulatory factor 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…Activity of CTLs is improved by 6 weeks of age and is similar to that of adult horses by 8 weeks . Antigen‐presenting cells from foals have significantly lower CD1 and MHC class II expression compared to that from adult horses . In addition, several studies have demonstrated that the ability of equine lymphocytes and neutrophils to produce or upregulate various cytokines, or both, is strongly influenced by age .…”
Section: Pathogenesis and Virulencementioning
confidence: 73%
“…Activity of CTLs is improved by 6 weeks of age and is similar to that of adult horses by 8 weeks . Antigen‐presenting cells from foals have significantly lower CD1 and MHC class II expression compared to that from adult horses . In addition, several studies have demonstrated that the ability of equine lymphocytes and neutrophils to produce or upregulate various cytokines, or both, is strongly influenced by age .…”
Section: Pathogenesis and Virulencementioning
confidence: 73%
“…On the basis of previous studies 15,20,21 to characterize cytokine profiles in PBMCs of healthy and sick foals, the β-actin gene was used as an internal reference gene to normalize the variation of cell numbers in the samples. On the basis of previous studies 15,20,21 to characterize cytokine profiles in PBMCs of healthy and sick foals, the β-actin gene was used as an internal reference gene to normalize the variation of cell numbers in the samples.…”
Section: Methodsmentioning
confidence: 99%
“…The disease typically manifests as a chronic pyogranulomatous inflammation in the form of broncopneumonia, enteritis and occasionally bacteremia and arthritis (Flaminio et al, 2009). Although many organisms can cause pneumonia in foals, infection with virulent Rhodococcus equi is considered to be the most common cause of severe pneumonia (Anon, 1978;Prescott, 1991;Takai et al, 1995).…”
Section: Introductionmentioning
confidence: 99%